2016
DOI: 10.1002/2016ja022989
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial noise emissions with a quasiperiodic modulation observed by DEMETER at harmonics of the O+ ion gyrofrequency

Abstract: The analysis of ionospheric equatorial noise (EN) with a quasiperiodic (QP) modulation observed by the Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions (DEMETER) spacecraft is presented. These EN emissions, also called whistler mode or fast magnetosonic waves, play an important role in acceleration of radiation belt electrons. A statistical analysis with 103 events shows that they occur just after intense magnetic storms. Usually, they are generated by unstable proton ring distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…A possible generation of a small fraction of the events inside the plasmasphere thus cannot be ruled out. We note that sporadic event observations well inside the plasmasphere are consistent with an analogous type of events observed at altitudes as low as 700 km (Parrot et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A possible generation of a small fraction of the events inside the plasmasphere thus cannot be ruled out. We note that sporadic event observations well inside the plasmasphere are consistent with an analogous type of events observed at altitudes as low as 700 km (Parrot et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Němec, Santolík, Hrbáčková, et al () further investigated high‐resolution Cluster Wideband Data for all 17 events where these were available, and they revealed the presence of a harmonic line structure in all of them. The emissions may occasionally consist of two frequency bands of interleaved QP elements (Li et al, ) and were also observed at altitudes as low as 700 km (Parrot et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…Through electric field observations of equatorial noise (magnetosonic waves) from IMP 6 and Hawkeye 1 satellites, Gurnett (1976) reported emissions of dominant spectral peaks at various proton gyrofrequency harmonics with minor peaks at one fourth and one eighth the proton gyrofrequency harmonics, that is, heavier ion harmonics. Parrot et al (2016) reported observations of equatorial noise emissions in the ionosphere with O+ harmonics. Recent observations of magnetosonic waves with CLUSTER (Walker et al, 2016), DEMETER (Santolík et al, 2016) and the Van Allen Probes (Min et al, 2018) reveal multiple spectral peaks in between the proton gyrofrequency harmonics, which could indicate resonance with heavier ions.…”
Section: Discussionmentioning
confidence: 99%
“…Out of them, 2,181 events were observed in the daytime half orbits and just 83 events were detected in the nighttime half orbits. Given that the events observed at low latitudes should be classified as QP modulated whistler mode equatorial noise (also known as fast magnetosonic waves) rather than QP emissions (Němec et al, , ; Parrot et al, ), we consider only QP events which at least partially spanned to geomagnetic latitudes larger than 40°. This leaves us with 2,172 events, out of which 79 were observed on the nightside.…”
Section: Data Setmentioning
confidence: 99%